2017
DOI: 10.1155/2017/4941379
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A Induces a Vascular Smooth Muscle Cell Phenotype Switch through the p38 MAPK Signaling Pathway

Abstract: Atherosclerosis is an important pathological condition which is accompanied by a vascular smooth muscle cell (VSMC) phenotype switch toward a synthetic phenotype. As an acute-phase protein, Serum Amyloid A (SAA) is thought to have a close relationship to atherosclerosis development. However, no study has investigated the direct effect of SAA on the VSMC phenotype switch, as well as the underlying mechanisms. The purpose of our study was to explore the effect of SAA on the VSMC phenotype switch and the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
3
25
0
2
Order By: Relevance
“…In addition, the acute-phase proteins serum amyloid A and C-reactive protein have been reported not to be solely produced by hepatocytes, but also in the arterial wall, by vascular smooth muscle cells (VSMCs). Both proteins stimulate the phenotypic switch of VSMCs into bone-like cells through activation of the p38 MAPK pathway and oxidative stress pathways [31,32]. As mentioned above, our study also revealed that, after proteomic analysis of aortic tissue from either IS or PCS exposed CKD rats, coagulation pathways (intrinsic/extrinsic prothrombin activation pathways) play a central role in the arterial calcification process [21].…”
Section: Inflammation and Coagulation Signaling Pathwayssupporting
confidence: 68%
“…In addition, the acute-phase proteins serum amyloid A and C-reactive protein have been reported not to be solely produced by hepatocytes, but also in the arterial wall, by vascular smooth muscle cells (VSMCs). Both proteins stimulate the phenotypic switch of VSMCs into bone-like cells through activation of the p38 MAPK pathway and oxidative stress pathways [31,32]. As mentioned above, our study also revealed that, after proteomic analysis of aortic tissue from either IS or PCS exposed CKD rats, coagulation pathways (intrinsic/extrinsic prothrombin activation pathways) play a central role in the arterial calcification process [21].…”
Section: Inflammation and Coagulation Signaling Pathwayssupporting
confidence: 68%
“…Results suggest that the activated p38MAPK signaling pathway plays a key role in the process of transformation of the VSMC phenotype from the dedifferentiated to differentiated state [56]. Some findings implied that the proliferative ability of VSMCs was also increased by serum amyloid (SAA) treatment via activation of p38 MAPK [57]. However, existing evidence shows that VSMC phenotypic switching was inhibited by pretreatment with the inhibitor of p38 MAPK [58].…”
Section: Discussionmentioning
confidence: 99%
“…6 While a detailed discussion of the mechanisms of myelin-associated inhibition of axonal outgrowth is outside the scope of this review, we refer the reader to a review by Zhang et al for more information. 23 There is also an accumulation of extracellular amino acids at the site of injury, whose abundance relates to severity of SCI and neurotoxicity. 22 These molecules are attractive targets for pharmacological intervention aimed at enhancing neuroprotection and neuroregeneration post-SCI and are discussed more in the following sections.…”
Section: Figmentioning
confidence: 99%